SYNTHESIS AND CHARACTERIZATION OF FILM LABELS USING ANTHOCYANIN FROM PURPLE SWEET POTATO SKIN (Ipomea Batatas L.) AS A QUALITY INDICATOR OF CHICKEN MEAT IN SMART PACKAGING - Arzeti Zainal; Diana Eka Pratiwi Eka Pratiwi; Hasri Hasri (Analit : Analytical and Environmental Chemistry, 2025)
The demand for smart packaging that provides real-time information on food freshness and safety continues to rise with growing consumer awareness of product quality. This study aimed to synthesize and characterize anthocyanin-based film labels from purple sweet potato peel (Ipomoea batatas L.) as freshness indicators for chicken meat. Anthocyanins were extracted via maceration using 96% ethanol acidified with 1% HCl and tested for color stability at pH 2–11. Films with 0%, 3%, 5%, and 7% anthocyanin concentrations were prepared. The films showed color changes from purple (pH 5.8) to greenish yellow (pH 8.7) with increasing meat pH, indicating spoilage. Physical tests revealed a water vapor transmission rate of 4.40 g/h·m², thickness of 0.08 mm, solubility of 40%, and biodegradability of 100%. FTIR analysis confirmed characteristic anthocyanin functional groups (O–H, C–H, C=C, aromatic C–H). Overall, the film shows potential as a natural and eco-friendly indicator for smart packaging to monitor chicken meat freshness.